The Effects of Mandatory Seat Belt Laws on Driving Behavior and Traffic Fatalities - Cohen, Alma; Einav, Liran (The Review of Economics and Statistics, 2003)
This paper investigates the effects of mandatory seat belt laws on driver behavior and traffic fatalities. Using a unique panel data set on seat belt usage in all U.S. jurisdictions, we analyze how such laws, by influencing seat belt use, affect the incidence of traffic fatalities. Allowing for the endogeneity of seat belt usage, we find that such usage decreases overall traffic fatalities. The magnitude of this effect, however, is significantly smaller than the estimate used by the National Highway Traffic Safety Administration. In addition, we do not find significant support for the compensating-behavior theory, which suggests that seat belt use also has an indirect adverse effect on fatalities by encouraging careless driving. Finally, we identify factors, especially the type of enforcement used, that make seat belt laws more effective in increasing seat belt usage.